2012
DOI: 10.1111/j.1600-051x.2012.01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Er:YAG laser treatment in supportive periodontal therapy

Abstract: Employing both sonic and laser treatment procedures during supportive periodontal care, similar clinical and microbiological outcomes can be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
2
30
0
1
Order By: Relevance
“…6 Ratka-Krüger et al 2012 [10] -Randomized controlled split mouth study -For better results, the speed of ultrasonic scalers, more efficient de-epithelization of Er:YAG lasers, and smooth root surface of hand instruments, should be combined, through using the three systems together. -There were no differences in microbiological outcomes or in bacterial recolonization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Ratka-Krüger et al 2012 [10] -Randomized controlled split mouth study -For better results, the speed of ultrasonic scalers, more efficient de-epithelization of Er:YAG lasers, and smooth root surface of hand instruments, should be combined, through using the three systems together. -There were no differences in microbiological outcomes or in bacterial recolonization.…”
Section: Discussionmentioning
confidence: 99%
“…The two treatment groups failed to reveal significant changes for most bacterial species, and they have indicated that both sonic and laser treatment procedures during supportive periodontal care are suitable to achieve similar clinical and microbiological outcomes [10]. Malali et al (2012) also concluded after comparing the effectiveness of Er:YAG laser with two formerly successful instruments, hand instruments, and ultrasonic scalers to determine the subgingival cell population changes in moderately deep and deep pockets, that, although Er:YAG lasers are clinically as efficient as hand instruments and ultrasonic scalers in treating periodontal disease, they do not seem to be notably superior to conventional systems.…”
Section: Antibacterial Effect Of the Conventional Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Supportive therapy is very important within a periodontal treatment regimen and this has been shown in several studies. 2,3 Oral hygiene reinforcement, scaling and root planing (SRP), polishing, chemical irrigation with antiseptic agents, local drug delivery with antibiotics like tetracycline fibers, low-level laser therapy (LLLT), photo dynamic therapy and other methods can be used for supportive periodontal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure of debridement generally aims to remove plaque accumulated inside the periodontal pocket by using manual equipment [20] [21] or ultrasonic waves [22]. In this study, revolutionary physicochemical methods, such as coldplasma treatment, are the reported methods used in attempts to eliminate periodontopathic bacterial layers deposited on the titanium surface.…”
Section: Introductionmentioning
confidence: 99%